2013
DOI: 10.1111/jvh.12160
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil–lymphocyte ratio: a novel predictor for short‐term prognosis in acute‐on‐chronic hepatitis B liver failure

Abstract: Acute-on-chronic hepatitis B liver failure (ACHBLF) has a poor prognosis in patients with hepatitis B virus infection. The role of the neutrophil-lymphocyte ratio (NLR), which reflects the inflammatory status of the patient before treatment, has never been studied in this setting. To investigate the predictive value of NLR in patients with ACHBLF, a retrospective cohort with 216 patients and a prospective validation cohort with 73 patients were recruited. Multivariate analyses showed that total bilirubin (TBIL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 33 publications
(35 reference statements)
4
46
0
2
Order By: Relevance
“…Previous studies found that a high baseline NLR was associated with poor treatment response in patients with hepatocellular carcinoma (HCC)[13] and increased risk of mortality in patients with acute pancreatitis or acute coronary syndrome[14, 15]. A few studies have examined the role of NLR in ACLF, but all excluded patients who received ALSS[16]. To our knowledge, this is the first study to shown that the NLR was an independent predictor of mortality in ALSS-treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that a high baseline NLR was associated with poor treatment response in patients with hepatocellular carcinoma (HCC)[13] and increased risk of mortality in patients with acute pancreatitis or acute coronary syndrome[14, 15]. A few studies have examined the role of NLR in ACLF, but all excluded patients who received ALSS[16]. To our knowledge, this is the first study to shown that the NLR was an independent predictor of mortality in ALSS-treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the cellular level, various immune imbalances have also emerged as biomarkers in NAFLD, from those in general white blood cells such as neutrophil-to-lymphocyte ratio (NLR), to specific lymphocytes subsets (22–24). The NLR expresses an imbalance in leukocytes with the dominance of neutrophils over lymphocytes and has been increasingly recognized as a predictor of outcomes in NAFLD (25), a role also shown in other chronic liver diseases such as viral hepatitis, liver cirrhosis, and HCC (2628). Another described cellular imbalance is what occurs at the CD4 + cells level with the dominance of T helper 17 (Th17) subset over the regulatory T (Treg) cells, which results from the polarization of the differentiation of T helper cells, also present in NAFLD and other chronic liver diseases (24, 2932).…”
Section: Introductionmentioning
confidence: 99%
“…(7,(20)(21)(22). It was reported that the N/L ratio was a poor prognostic factor in non-small cell lung cancer, acute-on-chronic hepatitis B liver failure, advanced pancreatic cancer, and biliary tract cancer (12)(13)(14)23). In patients with idiopathic dilated cardiomyopathy, the N/L ratio is associated with the severity of chronic heart failure (22).…”
Section: Discussionmentioning
confidence: 99%
“…White blood cell (WBC) counts, neutrophil counts, lymphocyte counts, age, sex, and mutation types of patients were extracted. The N/L ratio was calculated by dividing the absolute neutrophil counts with the absolute lymphocyte counts, obtained from the differential WBC count (12)(13)(14)(15)(16)(17).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation